Surface studies of Fe3O4(001), Fe/Ge(001) and Fe3O4(001)/Ge(001) - Jordan, Kenneth (Trinity College (Dublin, Ireland). School of Physics, 2006)
This work consists of surface studies of three systems; firstly, the (001) surface of a Fe3 O4 single crystal, secondly, the initial nucleation of Fe on the Ge(001) surface, and finally, iron oxide formed on Ge(001). The magnetite (001) surface was studied using Auger electron spectroscopy (AES), low energy electron diffraction (LEED), scanning tunneling microscopy (STM) and scanning tunneling spectroscopy (STS). The clean surface is shown to exhibit the (√2 x √2)R45° LEED mesh. The surface is imaged with tips made from both antiferromagnetic MnNi and non-magnetic W. An enhanced atomic scale contrast is imaged with the MnNi tips, which is explained in terms of a spin polarised contribution to the tunneling current. A model of the surface termination is put forward.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin